2008
DOI: 10.2478/s11756-008-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of partial resistance to powdery mildew in hexaploid wheat genotypes

Abstract: In the present study the degree of partial resistance (PR) of eleven hexaploid wheat (Triticum aestivum L.) genotypes was evaluated in laboratory (ratio of infection units in stage of second germ tube elongation versus stage of appressorium formation -ESH/App) and field conditions (calculating area under the disease progress curve -AUDPC). Based on the obtained data, genotypes with high degree of PR (Estica, GK Csornoc and Lívia), middle-resistant genotypes (Sana, Mv Vilma and Folio), genotypes with low portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A lot of researchers established that resistance based on Quantitative Trait Loci (QTL) or the combination of minor genes with effective race-specific genes provides long-term resistance to Blumeria graminis (DC) Speer f. sp. tritici (Miedaner and Flath 2007;Mikulová et al 2008;Bai et al 2012). According to the results of Chen et al (2009) the QTL QPm.osu.1A associated with the race-specific Pm3a allele.…”
Section: Cereal Research Communications 43 2015mentioning
confidence: 99%
“…A lot of researchers established that resistance based on Quantitative Trait Loci (QTL) or the combination of minor genes with effective race-specific genes provides long-term resistance to Blumeria graminis (DC) Speer f. sp. tritici (Miedaner and Flath 2007;Mikulová et al 2008;Bai et al 2012). According to the results of Chen et al (2009) the QTL QPm.osu.1A associated with the race-specific Pm3a allele.…”
Section: Cereal Research Communications 43 2015mentioning
confidence: 99%
“…Nevertheless, the high resistance level given by these genes is usually not durable, due to pathogen population evolution (Lillemo & Skinnes 2006). Protection observed in the sn398 and sn178 lines was similar to that conferred by conventional partial resistance genes in terms of reduction of pustule size, reduced production of spores and longer latency period of disease development (Hÿckelhoven 2005;Mikulová et al 2008). This resistance behaviour leads to a significantly reduced damage level when compared to a susceptible host plant by retarding the pathogen reproductive cycle.…”
Section: Discussionmentioning
confidence: 91%
“…Powdery mildew caused by Blumeria graminis f.sp. tritici is considered one of the most damaging for this crop in the world (Liu et al 2001;Lillemo & Skinnes 2006;Mikulová et al 2008;Zhang et al 2008;Chen et al 2009), and has caused yield losses ranging from 13 to 34% (Liu et al 2001;Lillemo & Skinnes 2006;Zhang et al 2008) despite control with fungicides and crop rotation. Race-specific resistance genes have been widely used in wheat breeding programs to control this disease, but the selection pressure exerted by new cultivars results in the rapid emergence of new pathotypes with the corresponding virulence genes (Liu et al 2001).…”
mentioning
confidence: 99%
“…Area under disease progress curve (AUDPC) is generally used to compare among treatments (Xu, 2006) and to evaluate the resistance of plant species to a pathogen (Mikulova et al, 2008). Jerger (2004) indicated that comparison of AUDPC among treatments is the most commonly used tool for evaluating practical disease management strategies.…”
Section: Area Under Disease Progress Curvementioning
confidence: 99%